19th International Plant Nutrition Colloquium - Rosolem, Ciro Antonio [UNESP]; Boaretto, Rodrigo M.; Moraes, Milton Ferreira (International Plant Nutrition Council, 2022)
O International Plant Nutrition Colloquium é organizado pelo International Plant Nutrition Council, formado por cientistas de todo o mundo que tenham contribuído significativamente para o campo da nutrição de plantas. O objetivo é avançar o conhecimento, a ciência e educação através de pesquisa não comercial, visando a produção de fibras, energia e alimento, segurança alimentar e sustentabilidade. O evento é realizado a cada quatro anos.O primeiro dia será dedicado ao Boro, depois serão quatro dias explorando os temas: Plant nutrition and food quality; Digital plant nutrition; The rhizosphere and plant nutrition; Plant-microorganism interaction and nutrient acquisition; Diagnosis of nutrient status and analytical methods; Breeding for a better plant nutrition; Biostimulants and plant nutrition; Nutrient uptake, transport and use efficiency; Nutrient availability in soils, toxicity and remediation; Nutrient cycling, agroecosystems and sustainability; Biotic stress and plant nutrition; New fertilizers and fertilizer recommendation; Plant nutrition, stress tolerance and climate change; Mineral nutrition of wild plants. A cada manhã e tarde, haverá uma sessão plenária, com apresentação de três temas gerais. Após, estão previstas três salas temáticas, explorando os temas do colóquio, com apresentação de alguns Key Note Speakers e de trabalhos voluntários, escolhido dentre os enviados pelos delegados.No último dia está programada uma excursão técnica à Cooperativa COAMO.Mais detalhes sobre o evento e a programação completa podem ser encontrados emwww.ipnc2022.com

Since its beginning in the early 1950s, the IPNC has grown to become the most important international meeting on fundamental and applied plant nutrition. Building on the success of previous IPNC meetings, more than 800 participants from all over the world was expected in Iguazu Falls. The main theme of the 19th International Plant Nutrition Colloquium is: "Stepping forward to Global Nutrient Use Efficiency". This theme has been chosen to highlight that plant nutrients, fundamental for successful intensification of global crop production can pose an environmental risk if not well used. This intensification is required to meet the demands of the future bio-based society for nutritious food, feed, raw materials, and energy. The colloquium has provided an excellent forum for the exchange and transfer of knowledge, information and ideas as well as for the creation of new collaborations and fostering synergies in the fields of plant mineral nutrition, plant molecular biology, plant genetics, agronomy, horticulture, ecology, environmental sciences and fertilizer use and production. We invite you to present the recent results of your research related to the different aspects of plant mineral nutrition.
Keywords: Plant nutrition; Nutrient use efficiency; Soil fertility; Rhizosphere; Fertilizers; Macronutrients; Micronutrients; Nutrição de plantas; Eficiência de uso de nutrientes; Fertilidade do solo; Risosfera; Macronutrientes; Micronutrientes